Liver Abscess in Patients With Leukemia and Prolonged Neutropenia. Issue 4 (July 2017) - Grabau, Michael; Pandya, Shuchi; Nanjappa, Sowmya; Shenoy, Rahul; Aslam, Sadaf; Greene, John N.
Abstract : Abstract: Patients with leukemia are at a high risk of developing disseminated invasive fungal and/or bacterial infections due to prolonged neutropenia, which is usually caused by myelosuppressive chemotherapy. Disseminated fungal infections in the setting of prolonged neutropenia result in high mortality. The most effective means to improve patient outcome is early diagnosis and treatment when preventive measures have failed. The most common fungal pathogens are Candida spp and Aspergillus spp. Rare causes of such infection are by Mucor and Entomopthorales spp, Fusarium spp, and Scedosporium spp, each having unique epidemiology, pathophysiology, and treatment options. We present a case of disseminated hepatic, pulmonary, bowel, and appendix mucormycosis successfully treated with antifungal therapy and without surgical intervention. We also review the literature regarding hepatic abscesses and disseminated invasive fungal infections along with current treatment strategies for Mucor infections. Abstract : The clinical symptoms of both fungal and bacterial dissemination are very similar. In the setting of prolonged neutropenia, abscesses in the liver and other organs are more likely to be of fungal origin. Certain fungi have unique patterns and characteristics that can help with radiological identifi cation. Fungal pathogens have the propensity to exhibit angioinvasion, causing tissue necrosis rather than pus, as seen with bacterial abscesses. Early diagnosis and preemptive antifungal therapy is crucial for improved outcomes. Supplemental digital content is available in the text.